Hubungan Spiritualitas dan Dukungan Sosial dengan Resiliensi Mahasiswa Sekolah Tinggi Diakones HKBP - Malau, Diana Christiany; Surbakti, Amanah; Murad, Abdul (Mahesa Research Center, 2022)
Empirically, this study aims to see the correlation between spirituality and social support with the resilience of HKBP Deaconess School Students. The population in this study was 120 people and the sample was 92 people where the sample was taken using random sampling. This type of research is a quantitative research with multiple regression analysis technique where the data collection uses questionnaire that is processed by the SPSS program. The results showed that:(1) There is a significant positive correlation between spirituality and social support with resilience, the coefficient value (Rx1x2y)= 0,604 and p = 0,000 < 0,010. The contribution of spirituality and social support can be seen from the coefficient of determination (R2) = 0,365 or 36,5 %. (2) There is a significant positive correlation between spirituality and resilience where the coefficient value (Rxy) = 0,538 with p = 0,000 < 0,010. The contribution of spirituality can be seen from the coefficient of determination (R2) = 0,2894 or 28,94 %. (3) There is a significant positive correlation between social support and resilience where the coefficient value (Rxy) = 0,503 with p = 0,000 < 0,010. The contribution of social support can be seen from the coefficient of determination (R2) = 0,253 or 25,3 %. Thus, it can be concluded that there is a significant correlation between spirituality and social support with the resilience of The HKBP Deaconess School students.